2021
DOI: 10.1021/acsami.0c22869
|View full text |Cite
|
Sign up to set email alerts
|

Activate Fe3S4 Nanorods by Ni Doping for Efficient Dye-Sensitized Photocatalytic Hydrogen Production

Abstract: Developing suitable catalysts capable of receiving injected electrons and possessing active sites for hydrogen evolution reaction (HER) is the key to building an efficient dyesensitized system for hydrogen production. Fe 3 S 4 is generally regarded as an inferior HER catalyst among the metal sulfide family, mainly due to its weak surface adsorption toward H atoms. In this work, we demonstrate a facile metal−organic frameworkderived method to synthesize uniform Fe 3 S 4 nanorods and active them for HER by Ni do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Compared with the Cu­(OH) 2 @FeOOH precursor, Cu­(OH) 2 @Fe 1 Ni 2.5 (OH) x showed a slight peak position change, indicating the interaction between the outer nanosheet array and the inner tube. In the spectrum of Figure a for Ni 2p, the peaks at 874.16 and 856.22 eV with two obvious shakeup satellites can be attributed to Ni 2p 1/2 and Ni 2p 3/2 , respectively, corresponding to the binding energy of Ni 2+ . , The predominant O 1s peak at 534.10 eV in Figure b is related to the metal-bonded surface hydroxyl groups. ,, The peaks at 534.50 and 535.29 eV in the O 1s spectrum of the Cu­(OH) 2 NTs and Cu­(OH) 2 @FeOOH are the oxygen in the hydroxyl group (Figure S4). These results confirm that the as-prepared core–shell nanoarrays are Cu­(OH) 2 @Fe 1 Ni 2.5 (OH) x with Fe and Ni in the oxidation states of Fe 3+ and Ni 2+ , respectively.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Compared with the Cu­(OH) 2 @FeOOH precursor, Cu­(OH) 2 @Fe 1 Ni 2.5 (OH) x showed a slight peak position change, indicating the interaction between the outer nanosheet array and the inner tube. In the spectrum of Figure a for Ni 2p, the peaks at 874.16 and 856.22 eV with two obvious shakeup satellites can be attributed to Ni 2p 1/2 and Ni 2p 3/2 , respectively, corresponding to the binding energy of Ni 2+ . , The predominant O 1s peak at 534.10 eV in Figure b is related to the metal-bonded surface hydroxyl groups. ,, The peaks at 534.50 and 535.29 eV in the O 1s spectrum of the Cu­(OH) 2 NTs and Cu­(OH) 2 @FeOOH are the oxygen in the hydroxyl group (Figure S4). These results confirm that the as-prepared core–shell nanoarrays are Cu­(OH) 2 @Fe 1 Ni 2.5 (OH) x with Fe and Ni in the oxidation states of Fe 3+ and Ni 2+ , respectively.…”
Section: Resultsmentioning
confidence: 96%
“…In the spectrum of Figure 4a for Ni 2p, the peaks at 874.16 and 856.22 eV with two obvious shakeup satellites can be attributed to Ni 2p 1/2 and Ni 2p 3/2 , respectively, corresponding to the binding energy of Ni 2+ . 43,47 The predominant O 1s peak at 534.10 eV in Figure 4b is related to the metal-bonded surface hydroxyl groups. 26,53,54 The peaks at 534.50 and 535.29 eV in the O 1s spectrum of the Cu(OH) 2 NTs and Cu(OH) 2 @FeOOH are the oxygen in the hydroxyl group (Figure S4).…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhang et al synthesized Ni-doped Fe 3 S 4 photocatalysts that revealed that Ni doping could adjust the electronic property of pure Fe 3 S 4 , optimize the surface adsorption energy toward H atoms, and enhance PHE activity. 11 Moreover, Deng and co-workers prepared Ni-doped g-C 3 N 4 photocatalysts, and the experimental results showed that Ni doping could increase light absorption, narrow the band gap, and restrain the recombination of carriers, thereby enhancing PHE activity. 12 In addition, some other Ni-doped semiconductor photocatalysts were also reported to exhibit great potential for H 2 evolution.…”
Section: Introductionmentioning
confidence: 99%